Answer: b= 11.2
10^2 + b^2 = 15^2
100 + b^2 = 225
b^2 = 125
b= 
b= 11.2
Step-by-step explanation:
Sorry, but the picture is too blurry. Can you write them down?
Answer:
this is kinda confusing..So ill just answer the first question.
<h3>Explanation: The Pythagorean Theorem gives us a2 + b2 = c2 for a right triangle, where c is the hypotenuse and a and b are the smaller sides.</h3>
hope it helps.
Answer:
C
Step-by-step explanation:
Take a careful look at a(n) = 6(-8)^(n-1).
The first term is 6. This is the result if we let n = 1; 6(-8)^0 = 6(1) = 6. Thus, we can immediately eliminate possible answer choices A and D.
What's the next term? Knowing that the first term, a(1), is 6, the next term is found by multiplying this 6 by (-8)^1, obtaining -48.
The next (third) term is found by multiplying this -48 by (-8)^2, obtaining -48*(+64), or - 3072.
Note that the sign of (-8)^(n-1) alternates, being odd when n-1 is odd and even when n-1 is even.
Answer C is the correct one.
40. Divide 81 by 41. 41 goes into 81 once with a remainder of 40